2010
DOI: 10.1182/blood-2009-10-251082
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of PI3K and mTOR inhibits autocrine and paracrine proliferative loops in PI3K/Akt/mTOR-addicted lymphomas

Abstract: Primary effusion lymphoma (PEL) constitutes a subset of non-Hodgkin lymphoma whose incidence is highly increased in the context of HIV infection. Kaposi sarcomaassociated herpesvirus is the causative agent of PEL. The phosphatidylinositol 3-kinase (PI3K) signaling pathway plays a critical role in cell proliferation and survival, and this pathway is dysregulated in many different cancers, including PEL, which display activated PI3K, Akt, and mammalian target of rapamycin (mTOR) kinases. PELs rely heavily on PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 48 publications
3
126
2
Order By: Relevance
“…PEL displays activated PI3K, Akt and mTOR. Although single modulation of the mTOR pathway inhibited PEL proliferation, it has been reported that dual inhibition of PI3K and mTOR was significantly more efficacious in culture and in a PEL xenograft tumour model [59]. These data provide important preclinical proof-of-concept on the suitability of targeting the PI3K/mTOR axis with specific inhibitors for the treatment of PEL in HIV-infected patients [59].…”
Section: Lymphomasmentioning
confidence: 79%
“…PEL displays activated PI3K, Akt and mTOR. Although single modulation of the mTOR pathway inhibited PEL proliferation, it has been reported that dual inhibition of PI3K and mTOR was significantly more efficacious in culture and in a PEL xenograft tumour model [59]. These data provide important preclinical proof-of-concept on the suitability of targeting the PI3K/mTOR axis with specific inhibitors for the treatment of PEL in HIV-infected patients [59].…”
Section: Lymphomasmentioning
confidence: 79%
“…Targeting multiple intermediates along the PI3K/AKT/mTOR axis may overcome this potential problem. [75][76][77] Most of the small molecule inhibitors that target mTORC1/2 also target other proteins in the PI3K/AKT/ mTOR signaling pathway, including PI3K, and are discussed in section 4.3. As with many kinase inhibitors, these agents can also affect other kinase pathways at higher concentrations, but the half maximal inhibitory concentration (IC50) values for mTOR kinase for many of these drugs, including PP242, are nearly 100-fold lower than their affinity for other kinases.…”
Section: Mtor Kinase Inhibitors (Mtorc1/2 Inhibitors)mentioning
confidence: 99%
“…NVP-BEZ235 is a pan-PI3K inhibitor that acts against all of the isoforms of PI3K and PI3K mutants. Previous studies have demonstrated the efficacy of NVP-BEZ235 as an antitumor agent in vitro and in vivo in glioblastoma, multiple myeloma, melanoma, lymphoma, www.nature.com/aps Pal I et al Acta Pharmacologica Sinica npg sarcoma, breast, lung, and ovarian cancer models [84][85][86][87][88][89][90][91][92][93] . In the case of colon cancer, NVP-BEZ23 decreases cellular proliferation and causes sustained inhibition of mTORC1 and mTORC2 with a transient PI3K blockade with no subsequent effect on apoptosis either in vitro or in vivo in a GEM model.…”
Section: Current Progress In Clinical Trialsmentioning
confidence: 99%